To solve the equation x/3 - 9 = 6 for x, we can start by isolating the variable x by performing the following steps:
1. Add 9 to both sides of the equation: x/3 - 9 + 9 = 6 + 9
Simplifying, we get: x/3 = 15
2. Multiply both sides of the equation by 3 to clear the fraction: 3(x/3) = 3(15)
Simplifying, we get: x = 45
Therefore, the solution to the equation x/3 - 9 = 6 is x = 45.
What is the solution of the equation x/3 — 9 = 6 solving for x? (1 point)
7 answers
Randall needs to solve the equation 5x + 8 = 63. His first mathematical operation used to isolate x is subtraction.
Which value will he apply it to? (1 point)
Which value will he apply it to? (1 point)
To isolate x in the equation 5x + 8 = 63, Randall will apply subtraction to the constant term on the same side as the variable x. In this equation, the constant term is 8. So, Randall will subtract 8 from both sides of the equation.
Marion is solving the equation 9x - 6 = 12. As a first step, she adds 6 to both sides of the equation. In the next
step, by what value does each side need to be divided? (1 point)
step, by what value does each side need to be divided? (1 point)
To solve the equation 9x - 6 = 12, Marion adds 6 to both sides as a first step. After adding 6, the equation becomes 9x = 18.
In the next step, Marion needs to divide each side of the equation by a value to isolate the variable x. To do this, she needs to divide each side by the coefficient of x, which is 9.
So, each side of the equation needs to be divided by 9 in the next step.
In the next step, Marion needs to divide each side of the equation by a value to isolate the variable x. To do this, she needs to divide each side by the coefficient of x, which is 9.
So, each side of the equation needs to be divided by 9 in the next step.
Bernal is solving the equation y/7-3=39.
As a first step, he starts by adding _______ to both sides of the equation, and then continues by multiplying by ________ on each side.
As a first step, he starts by adding _______ to both sides of the equation, and then continues by multiplying by ________ on each side.
To solve the equation y/7 - 3 = 39, Bernal needs to perform the following steps:
First, he starts by adding 3 to both sides of the equation. This will eliminate the -3 on the left side:
y/7 - 3 + 3 = 39 + 3
Simplifying, we get: y/7 = 42
Next, to isolate the variable y, Bernal needs to multiply each side of the equation by 7, which is the denominator of the fraction on the left side:
7(y/7) = 42 * 7
Simplifying, we get: y = 294
Therefore, Bernal adds 3 to both sides in the first step and then multiplies both sides by 7 in the second step to solve the equation y/7 - 3 = 39.
First, he starts by adding 3 to both sides of the equation. This will eliminate the -3 on the left side:
y/7 - 3 + 3 = 39 + 3
Simplifying, we get: y/7 = 42
Next, to isolate the variable y, Bernal needs to multiply each side of the equation by 7, which is the denominator of the fraction on the left side:
7(y/7) = 42 * 7
Simplifying, we get: y = 294
Therefore, Bernal adds 3 to both sides in the first step and then multiplies both sides by 7 in the second step to solve the equation y/7 - 3 = 39.